2014
DOI: 10.1097/ajp.0b013e3182934b8d
|View full text |Cite
|
Sign up to set email alerts
|

Paraspinal Stimulation Combined With Trigger Point Needling and Needle Rotation for the Treatment of Myofascial Pain

Abstract: This study highlighted the greater efficacy of MDIMST over the placebo-sham and LTrP-I and indicated that both active treatments are more effective than placebo-sham for MPS associated with limitations in active and routine activities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
50
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 49 publications
(54 citation statements)
references
References 42 publications
(45 reference statements)
3
50
0
1
Order By: Relevance
“…The number of patients in each study group was determined by previous clinical trials [32]. An a priori estimate indicated that a total sample size of 57 patients divided into three balanced treatment groups (n = 19) was needed to detect a 1.4-cm reduction (average standard deviation 1.2 cm) in pain intensity associated with melatonin or placebo at power and α levels of 0.8 and 0.01, respectively [33]; such a reduction would be clinically relevant and comparable to other pharmacological interventions.…”
Section: Methodsmentioning
confidence: 99%
“…The number of patients in each study group was determined by previous clinical trials [32]. An a priori estimate indicated that a total sample size of 57 patients divided into three balanced treatment groups (n = 19) was needed to detect a 1.4-cm reduction (average standard deviation 1.2 cm) in pain intensity associated with melatonin or placebo at power and α levels of 0.8 and 0.01, respectively [33]; such a reduction would be clinically relevant and comparable to other pharmacological interventions.…”
Section: Methodsmentioning
confidence: 99%
“…However, studies in which acupuncture was applied in patients with muscle pain in the upper trapezius [49] or with nonspecific low back pain [21] pointed out that the real acupuncture therapy was more effective than placebo acupuncture for pain relief.…”
Section: Discussionmentioning
confidence: 99%
“…However, in addition to regional pain, local tenderness in trigger points and loss of joint function, MPS may also be associated with psychiatric complications such as anxiety, sleeplessness and depression. 31 Only two studies, namely those by Couto et al 19 and Tekin et al, 20 examined for any improvement in mental health.…”
Section: Overall Completeness and Applicability Of Evidencementioning
confidence: 99%